2010
DOI: 10.1002/dc.21306
|View full text |Cite
|
Sign up to set email alerts
|

Testicular leydig cell tumor diagnosed on fine needle aspiration

Abstract: We report on the cytopathologic findings of a Leydig cell tumor of the testis in an adult male with no evidence of endocrine dysfunction. The preoperative diagnosis was based on fine needle aspiration cytology (FNAC) and was subsequently confirmed on histomorphology. The cytologic smears were cellular and showed tumor cells arranged singly, as well as in dyscohesive clusters. The tumor cells were large, round to polygonal, with indistinct cytoplasmic margins and pale, abundant, granular to vacuolated cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Epididymis, cord involvement and vascular invasion is frequent 1. Although FNAC in testicular tumour is feared to be associated with probable scrotal violation,2 FNAC has been explored in the diagnosis of lymphoma, Leydig and Sertoli cell tumours 3 4. Fear of needle trauma and local tumour implantation as well as lack of information on interstitial tissue and tubular basement membrane on FNAC smears are the drawbacks considered with FNAC in testicular tumours 2.…”
Section: Discussionmentioning
confidence: 99%
“…Epididymis, cord involvement and vascular invasion is frequent 1. Although FNAC in testicular tumour is feared to be associated with probable scrotal violation,2 FNAC has been explored in the diagnosis of lymphoma, Leydig and Sertoli cell tumours 3 4. Fear of needle trauma and local tumour implantation as well as lack of information on interstitial tissue and tubular basement membrane on FNAC smears are the drawbacks considered with FNAC in testicular tumours 2.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fine needle aspiration for diagnosis may be an alternative to more invasive biopsy procedures in the preoperative diagnosis of this rare testicular tumor [14]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Reinke crystals were much better appreciated on air‐dried smears than on fixed smears or tissue sections. In smears, the crystals were numerous and observed both in the cytoplasm and the nucleus of Leydig cells 7,8,15 . Leydig cell tumors can also be diagnosed intraoperatively.…”
Section: Reinke Crystal Visualizationmentioning
confidence: 99%
“…In smears, the crystals were numerous and observed both in the cytoplasm and the nucleus of Leydig cells. 7,8,15 Leydig cell tumors can also be diagnosed intraoperatively.…”
Section: Reinke Crystal Visualizationmentioning
confidence: 99%
See 1 more Smart Citation